Human and Animal Models for Translational Research on Neurodegeneration: Challenges and Opportunities From South America - Adolfo M. García (Frontiers Research Topics, 2018)
Neurodegenerative diseases are the most frequent cause of dementia, representing a burden for public health systems (especially in middle and middle-high income countries). Although most research on this issue is concentrated in first-world centers, growing efforts in South America are affording important breakthroughs. This emerging agenda poses new challenges for the region but also new opportunities for the field. This book aims to integrate the community of experts across the globe and the region, and to establish new challenges and developments for future investigation. We present research focused on neurodegenerative research in South America. We introduce studies assessing the interplay among genetic, neural, and behavioral dimensions of these diseases, as well as articles on vulnerability factors, comparisons of findings from various countries, and works promoting multicenter and collaborative networking. More generally, our book covers a broad scope of human-research approaches (behavioral assessment, neuroimaging, electromagnetic techniques, brain connectivity, peripheral measures), animal methodologies (genetics, epigenetics, proteomics, metabolomics, other molecular biology tools), species (all human and non-human animals, sporadic, and genetic versions), and article types (original research, review, and opinion papers). Through this wide-ranging proposal, we hope to introduce a fresh approach to the challenges and opportunities of research on neurodegeneration in South America.